Urological complications of inguinal hernia surgery. Issue 2 (May 2013) - Shah, S; Marsh, H; Khan, MS; Shah, A; Madaan, S
Background and aims: A systematic review of the literature is presented with regard to urological complications resulting from inguinal hernia surgery. Considering the amount of inguinal hernia operations performed, the resulting complications, which may be urological in presentation, have potential late irreversible and medico-legal implications. Methods and results: A Pubmed search of 'urological' 'complications' and 'inguinal hernia surgery' was carried out and clinical practice was also taken into consideration. Discussion: Approximately 75% of hernias occur in the groin; two-third of these are indirect and about one-third direct. Most of these repairs are carried out by the general surgeons and any complication, including urological, are often initially managed by the operating general surgeon. Often a urological opinion is sought late for conditions which may be reversible. We present potential urological complications, their presenting features and management. Conclusion: Recognition, timely referral and appropriate treatment of urological complications after hernia surgery are necessary to avoid potential consequences and long-term morbidity.